NMDA receptors are expressed in human ovarian cancer tissues and human ovarian cancer cell lines - North WG; Liu F; Tian R; Abbasi H; Akerman B (Dove Medical Press, 2015)
William G North, Fuli Liu, Ruiyang Tian, Hamza Abbasi, Bonnie Akerman Department of Physiology and Neurobiology, Geisel School of Medicine at Dartmouth College, Lebanon, NH, USA Abstract: We have earlier demonstrated that breast cancer and small-cell lung cancer express functional NMDA receptors that can be targeted to promote cancer cell death. Human ovarian cancer tissues and human ovarian cancer cell lines (SKOV3, A2008, and A2780) have now been shown to also express NMDA-receptor subunit 1 (GluN1) and subunit 2B (GluN2B). Seventeen ovarian cancers in two arrays were screened by immunohistochemistry using polyclonal antibodies that recognize an extracellular moiety on GluN1 and on GluN2B. These specimens comprised malignant tissue with pathology diagnoses of serous papillary cystadenocarcinoma, endometrioid adenocarcinoma, and clear-cell carcinoma. Additionally, archival tissues defined as ovarian adenocarcinoma from ten patients treated at this institute were also evaluated. All of the cancerous tissues demonstrated positive staining patterns with the NMDA-receptor antibodies, while no staining was found for tumor-adjacent normal tissues or sections of normal ovarian tissue. Human ovarian adenocarcinoma cell lines (A2008, A2780, SKOV3) were demonstrated to express GluN1 by Western blotting, but displayed different levels of expression. Through immunocytochemistry utilizing GluN1 antibodies and imaging using a confocal microscope, we were able to demonstrate that GluN1 protein is expressed on the surface of these cells. In addition to these findings, GluN2B protein was demonstrated to be expressed using polyclonal antibodies against this protein. Treatment of all ovarian cell lines with antibodies against GluN1 was found to result in decreased cell viability (P<0.001), with decreases to 10%–25% that of untreated cells. Treatment of control HEK293 cells with various dilutions of GluN1 antibodies had no effect on cell viability. The GluN1 antagonist MK-801 (dizocilpine maleate) and the GluN2B antagonist ifenprodil, like antibodies, dramatically decreased the viability of A2780 ovarian tumor cells (P<0.01). Treatment of A2780 tumor xenografts with ifenprodil (2.5 mg/kg body weight/day) significantly reduced tumor growth in nu/nu mice. Our findings suggest that both GluN1 and GluN2B proteins as membrane components could be readily available targets for the treatment of most ovarian cancers. Keywords: ovarian cancer, NMDA receptors, inhibitors, antibodies, potential therapy